Automatic target classification in a low frequency FSR network - Abdul Rashid, Nur Emileen; Antoniou, Michail; Jancovic, Peter; Sizov, Vladimir; Raja Abdullah, Raja Syamsul Azmir; Cherniakov, Mike (IEEE, 2008)
This paper presents the evaluation of a low-frequency Forward Scattering Radar (FSR) network for the classification of ground targets. The experimental results of automatic targets classification for different operational frequencies are presented and discussed. The possibility of target recognition is shown for system operating frequencies in the VHF band.